Risk mitigation strategies in exports to markets with exchange restrictions: an integrative review - Barmak, Gaspar (Revista JRG de Estudos Acadêmicos, 2025)
This article presents an integrative literature review on risk mitigation strategies in exports to markets with exchange restrictions. A total of 52 publications were analyzed, including peer-reviewed articles and institutional reports from international organizations, published between 2000 and 2025. The results were organized into three main axes: (i) financial strategies, such as derivatives, natural hedging, and currency invoicing; (ii) operational and contractual strategies, involving exchange rate adjustment clauses, shorter payment terms, and geographic diversification; and (iii) institutional instruments, such as letters of credit, export credit insurance, and support from export credit agencies. The analysis revealed that there is no single solution to risk mitigation in contexts of exchange restrictions, but rather a need for hybrid strategies that combine financial, contractual, and institutional mechanisms. It is concluded that the alignment between business practices and public policies is essential to reduce transaction costs and ensure international competitiveness, especially for small and medium-sized enterprises.